1977
DOI: 10.1136/ard.36.1.74
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intra-articular corticosteroid injections on primate cartilage.

Abstract: for the experiment. Throughout the study they were fed a pathogen-free balanced diet suitable for humans. Using strict aseptic precautions and with the animals sedated with phencyclidine or ketamine hydrochloride, 0 5 ml (20 mg) methyl prednisolone was injected into one knee joint of each animal. An equivalent volume of vehicle used in the same commercial preparation of methyl prednisolone was injected into the opposite knee. The vehicle consisted ofpolyethylene glycol 29 mg, sodium chloride 8f7 mg, mynistylga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
0

Year Published

1981
1981
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(27 citation statements)
references
References 26 publications
0
27
0
Order By: Relevance
“…The differences in our observations compared with those of the others may be multifactorial. Generalization regarding nonprimate cartilage used in the above studies of human cartilage may not be possible [20]. The cytoarchitecture of cartilage in rabbit medial femoral condyles, for example, has a much higher density of chondrocytes when compared with human cartilage [17].…”
Section: Discussionmentioning
confidence: 99%
“…The differences in our observations compared with those of the others may be multifactorial. Generalization regarding nonprimate cartilage used in the above studies of human cartilage may not be possible [20]. The cytoarchitecture of cartilage in rabbit medial femoral condyles, for example, has a much higher density of chondrocytes when compared with human cartilage [17].…”
Section: Discussionmentioning
confidence: 99%
“…However, the repeated use of IA corticosteroid in nonprimates has been associated with limited cartilage damage (37,38). Studies using both in vitro human cartilage explants and primate models have not demonstrated long-term adverse effects on cartilage (39,40). Despite large numbers of intrasynovial injections over the years, there are relatively few anecdotal reports of glucocorticoid arthropathy in humans (41).…”
mentioning
confidence: 99%
“…Mankin et a1 (24) showed that IA steroids administered to rabbits, impaired cartilage synthesis and accelerated cartilage fissuring. In contrast, repeated IA steroid injections appeared to have no detrimental effect in monkeys (25). Moreover, the effects of IA steroids on synovium, which is considered the major tissue responsible for the synthesis of SF HA and which may control the rate of clearance of HA from the joint, are not well documented.…”
mentioning
confidence: 92%